Dynamic Relationships between Democracy and Tax Revenues: The Case of Turkiye - Kanca, Osman Cenk; Yamak, Rahmi (International Journal of Economics and Financial Issues, 2025)
There is an extensive body of literature emphasizing the relationship between democracy and taxation. However, studies investigating the relationship between democracy and specific types of tax revenues remain limited. This study explores the extent to which democracy influences various categories of tax revenues in Turkiye. Utilizing a sample specifically composed for Turkiye covering the years 2006-2023, it was found that democracy negatively impacts income and corporate tax revenues. These findings align with the predictions of the conflict approach. Conversely, the positive relationship observed between democracy and both indirect and direct tax revenues supports the compatibility approach. Meanwhile, the neutral relationship between total tax revenues and democracy aligns with the skeptical approach. According to the study’s findings, there is a statistically significant causal relationship between corporate tax revenues, indirect tax revenues, direct tax revenues, and democracy.